CHARACTERISTICS OF ROAD TRAFFIC ACCIDENTS CAUSES, INJURIES AND OUTCOMES ENCOUNTERED IN FAISALABAD BETWEEN 2016-2019 - Nazim Hayat; Samia Rasool Tabassum; Yasir Riaz Gillani; Nadia Bano; Irshad Ahmed; Saira Saleem (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Road traffic accidents are the ninth leading cause of death worldwide, contributing significantly to global disease burden. Emergency Medical services(EMS) play a role in minimizing the morbidity and mortality. Our objective was to determine the characteristics of injury pattern and causes encountered in Road Traffic crashes (RTCs) managed by 1122 in Faisalabad Pakistan andto access the outcome of these accidents. METHODOLOGY: All Road Traffic crashes and victims in Faisalabad city of Pakistan which were initially managed by Rescue 1122 between 2016 to 2019 were included in the study. Total sample size was 101995. It is descriptive cross-sectional study which includes patients of different ages, sex and motor-vehicles accidents having different injury sites. RESULTS: During the study period there were total 101995 RTCs victims to whom emergency medical services (EMS) were provided. Gender wise 80.73% male victims and 19.27% female victims. Major age groups were between 21-30 years (25.917%). The major risk factors of accidents were over-speeding (56.8%) followed by carelessness (18.32%), wrong turn (8.69%) , u-turn(5.84%) , one wheeling(0.008%), tyre burst (0.117%) and others(10.14%). The injuries frequently encountered are minor which accounts for (44.68%), Single fracture (23.25%), Multiple fracture (16.62%), Head injury (12.40%) and Spinal injury(3.03%). Outcome of RTCs in our study was alive & unstable (54.47%), alive & stable (44.7%) and dead (0.83%). CONCLUSION: This study showed that Road Traffic Accident are the major public health problem in our society and contributes markedly to high morbidity and mortality. Urgent Preventive measures including community education should be established to reduce the risk of their outcome.